2020
DOI: 10.1016/j.neuron.2019.10.030
|View full text |Cite
|
Sign up to set email alerts
|

A Basal Forebrain-Cingulate Circuit in Macaques Decides It Is Time to Act

Abstract: The medial frontal cortex has been linked to voluntary action, but an explanation of why decisions to act emerge at particular points in time has been lacking. We show that, in macaques, decisions about whether and when to act are predicted by a set of features defining the animal's current and past context; for example, respectively, cues indicating the current average rate of reward and recent previous voluntary action decisions. We show that activity in two brain areas-the anterior cingulate cortex and basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
171
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(184 citation statements)
references
References 85 publications
13
171
0
Order By: Relevance
“…1E). Previous investigations have shown that the timing of the next action that a rat or macaque makes is related to the timing of recent previous actions (5,14). Therefore, in addition to the present context, we also investigated whether the outcomes and action times of recent past trials influenced human participants' action time on the current trial.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…1E). Previous investigations have shown that the timing of the next action that a rat or macaque makes is related to the timing of recent previous actions (5,14). Therefore, in addition to the present context, we also investigated whether the outcomes and action times of recent past trials influenced human participants' action time on the current trial.…”
Section: Resultsmentioning
confidence: 95%
“…to Act. Having shown that contextual factors influence decision time to act, we next used a Cox proportional hazard model to estimate actTime, at each trial, from present and past contextual factors (5,14). Specifically, we asked how much time (in seconds) would pass before a participant decided to respond, given present and past contextual factors.…”
Section: Contextual Factors Explained a Large Proportion Of Variance mentioning
confidence: 99%
See 2 more Smart Citations
“…Protocols 2 and 3 in monkeys: Decision to act task. The experimental task used in protocol 2 is described in detail elsewhere (64). Briefly, the task was designed to investigate how contextual factors and internal state, shaped by present and past environment, are integrated to influence whether and when to act.…”
Section: Experimental Tasksmentioning
confidence: 99%